High Resistivity of Single Crystal CsPbBr3 Semiconductor for Radiation Detection via Proposed Temperature‐Concentration Balance Method - Xuebao Zhang; Qingbo Wang; Ying Gao; Junying Zhang; Youpeng Wu; Peijie Ma; Lin Ma; Jianing Cai; Fenglei Niu; Qiang Zhao; Yunchao Tang; Junwei Bian; et al. (Advanced Electronic Materials)
Abstract Lead halide perovskites have shown high performance in radiation detection techniques owing to their excellent optoelectronic properties and stability. However, the high resistivity of the CsPbBr3 radiation detector is intensively dependent on the growth quality of the single crystal, which is closely related to temperature gradients or the introduction of additives. Herein, a CsPbBr3 single crystal with high radiation performance is grown based on the proposed temperature‐concentration balance (TCB) method. The prepared perfect single crystal remains high quality in repeated experiments, which belongs to the Pnma space group, benefiting from the effective growth method. Based on the CsPbBr3 single crystal, the fabricated detector with the asymmetrical Au‐In electrodes demonstrates outstanding linearity under reverse bias. It exhibits a lower dark current (2.66 × 10−2 nA) and high resistivity, which helps acquire a broader radiation measurement range. Moreover, the emission spectrum of the CsPbBr3 single crystals exhibits a sharp emission peak at 527 nm and narrower full width at half maximum, making crystals easily couple into radiation detectors. These findings provide insight into the growth and regulation of CsPbBr3 crystal for more extensive applications in radiation detection in the future.